Venlafaxine’s therapeutic reference range in the treatment of depression revised: a systematic review and meta-analysis: original investigation - Lense, Xenija M.; Hiemke, Christoph; Funk, Cleo; Havemann-Reinecke, Ursula; Hefner, Gudrun; Menke, A.; Mößner, Rainald; Riemer, Thomas Günther; Scherf-Clavel, Maike; Schoretsanitēs, Geōrgios; Gründer, Gerhard; Hart, Xenia Marlene (Psychopharmacology, 2024)
The selective serotonin and norepinephrine reuptake inhibitor venlafaxine is among the most prescribed antidepressant drugs worldwide and, according to guidelines, its dose titration should be guided by drug-level monitoring of its active moiety (AM) which consists of venlafaxine (VEN) plus active metabolite O-desmethylvenlafaxine (ODV). This indication of therapeutic drug monitoring (TDM), however, assumes a clear concentration/effect relationship for a drug, which for VEN has not been systematically explored yet.